Porous Cr2O3 bead with a 3D continuous pore architecture: synthesis and its catalytic performance for decomposition of ammonium perchlorate. (18th June 2019) - Wang, Dakang; Jiang, Yanqiu; Hu, Yinghui; Hao, Dongyu; Yang, Yulin; Fan, Ruiqing; Xia, Debin; Lin, Kaifeng
Abstract : Mesoporous/macroporous Cr2 O3 beads with 3D continuous pore structure exhibit improved thermal decomposition of ammonium perchlorate compared with Cr2 O3 crystals. Abstract : A mesoporous/macroporous Cr2 O3 bead with the size of 0.2–0.3 mm and a 3D continuous pore structure (Cr2 O3 -MPB) was synthesized using an anion exchange resin as a hard template for the first time. Its structural characteristics were tested by scanning electron microscopy, X-ray diffraction, nitrogen adsorption–desorption and transmission electron microscopy, and the results showed that the 3D continuous pores of Cr2 O3 -MPB are mesoporous and macroporous with size mainly distributed in the range of 20–90 nm. The obtained Cr2 O3 -MPB was then used to catalyze the thermal decomposition of ammonium perchlorate (AP) and proved to reduce the AP thermal decomposition temperature in HTD from 411.8 °C to 337.8 °C and increase the exotherm from 450.3 J g −1 to 1203.5 J g −1 . Notably, the advantage of the bead sample was confirmed by comparison with the commercial Cr2 O3, illustrating that the 3D continuous pore structure of Cr2 O3 -MPB plays a vital role in promoting the AP thermal decomposition by enhanced mass transfer in it. Such a bead might show potential as an efficient combustion catalyst in solid rocket propellants.